2022
DOI: 10.2196/37775
|View full text |Cite
|
Sign up to set email alerts
|

Actions Speak Louder Than Words: Sentiment and Topic Analysis of COVID-19 Vaccination on Twitter and Vaccine Uptake

Abstract: Background The lack of trust in vaccines is a major contributor to vaccine hesitancy. To overcome vaccine hesitancy for the COVID-19 vaccine, the Australian government launched multiple public health campaigns to encourage vaccine uptake. This sentiment analysis examines the effect of public health campaigns and COVID-19–related events on sentiment and vaccine uptake. Objective This study aims to examine the relationship between sentiment and COVID-19 vaccine uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Our result is different from Wang et al [18] and Melton et al [19] who reported that in general, public in United States of America tend to react positively toward COVID-19 vaccine and the positive sentiment increased as more people got vaccinated. Our results are also different from Yousef et al [16] who demonstrated that negative sentiment was dominated in their dataset on Australia vaccination program on Twitter. Nevertheless, our result was similar with Choi et al [38] who demonstrated that public sentiments towards COVID-19 vaccines in South Korea were dominated by neutral sentiment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our result is different from Wang et al [18] and Melton et al [19] who reported that in general, public in United States of America tend to react positively toward COVID-19 vaccine and the positive sentiment increased as more people got vaccinated. Our results are also different from Yousef et al [16] who demonstrated that negative sentiment was dominated in their dataset on Australia vaccination program on Twitter. Nevertheless, our result was similar with Choi et al [38] who demonstrated that public sentiments towards COVID-19 vaccines in South Korea were dominated by neutral sentiment.…”
Section: Discussioncontrasting
confidence: 99%
“…Analyzing public sentiments using existing sentiment analysis tools or lexicons have also been explored in previous work. Yousef et al [16] examined the effect of public health campaigns and COVID-19 related events on sentiment and vaccine uptake, while the sentiment was identified using AI-based tool, BytesView. Shim et al [17] analyzed changes in public perception of COVID-19 vaccines in Korea using Korean sentiment lexicon.…”
Section: Related Workmentioning
confidence: 99%
“…Some scholars have found a relationship between emotions and vaccination rates through sentiment analysis, and Yousef et al found that the higher the incidence of negative emotions in public vaccination, the higher the vaccination rate [73]. Chien et al found that trends in public vaccination emotions were significantly associated with increasing trends in vaccination rates and falling trends in COVID-19 case growth and morbidity and mortality rates [74].…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Vaccine hesitancy is a psychological state of resistance or hesitation to vaccination, and vaccine hesitation individuals have some degree of negative emotions such as worry, fear, and resistance to vaccination or the vaccine itself. Previous studies have also found that social media texts about the COVID-19 vaccine are mostly dominated by negative emotions [70,73,74]. The "Individual rights" is the most negative of all types, as posts in this type are usually expressed as the act or requirement of being forced to receive the vaccine, which can cause users to feel antipathy and resistance to vaccination.…”
Section: Disscussonmentioning
confidence: 99%
“…A recent survey shows that unvaccinated Americans felt too much pressure to receive a COVID-19 vaccine, leading to unwillingness and resistance (Pew Research Center, 2021b). In addition, scholars using sentiment analysis of social media content about COVID-19 vaccination found that distrust and safety concerns related to COVID-19 vaccination were still prevalent (Ansari and Khan, 2021; Melton et al , 2021), and that negative views prevailed (Yousef et al , 2022). Resistance to social marketing campaigns can seriously undermine persuasion (Petrova and Cialdini, 2011); therefore, crafting strategic and effective messages that attenuate negative responses to COVID-19 vaccination promotion is crucial to effective social marketing communication.…”
mentioning
confidence: 99%